Electrons, Localization but no Hopping: Disorder as Key for Understanding Charge Transport in Mesoporous Silicon - Tommy Hofmann; Haider Haseeb; Danny Kojda; Natalia Gostkowska‐Lekner; Klaus Habicht (Small Structures)
This article presents a unique study on the charge carrier transport in electrochemically anodized mesoporous silicon by combining macroscopic conductivity and thermopower measurements. Temperature‐dependent electrical conductivity measurements reveal a thermally activated transport in extended electronic states. An intrinsic variation of the thermal activation energies from sample to sample upon apparent identical synthesis conditions is discussed in terms of microscopic disorder. In a detailed analysis of the activation energies, the existence of a disorder‐dependent mobility edge between localized and extended states in a band tail with exponential density‐of‐states becomes indispensable for understanding the microscopic transport mechanism. The observation of a Meyer–Neldel compensation rule for the conductivity between different samples is a direct consequence of this mobility edge. Temperature‐dependent thermopower measurements provide further, stringent proof for disorder‐dominated transport in extended states above the mobility edge and dispel an alternative explanation attempt for the Meyer–Neldel rule in mesoporous silicon based on multiphonon absorption upon charge carrier transport.